Endoplasmic reticulum stress alters myelin associated protein expression and extracellular vesicle composition in human oligodendrocytes - Evalt, Ethan D.; Govindaraj, Saranraj; Jones, Madison T.; Ozsoy, Nesve; Chen, Han; Russell, Ashley E. (Frontiers in Molecular Biosciences, 2024)
Myelination of the central nervous system is mediated by specialized glial cells called oligodendrocytes (OLs). Multiple sclerosis (MS) is characterized by loss of myelination and subsequent clinical symptoms that can severely impact the quality of life and mobility of those affected by the disease. The major protein components of myelin sheaths are synthesized in the endoplasmic reticulum (ER), and ER stress has been observed in patients with MS. Extracellular vesicles (EVs) have been shown to carry bioactive cargo and have the potential to be utilized as noninvasive biomarkers for various diseases. In the current study, we sought to determine how ER stress in OLs affected the production of key myelination proteins and EV release and composition. By inducing ER stress in a human oligodendroglioma cell line, we observed significant reductions in the expression of myelination proteins and alterations to autophagosome formation. We separated EVs from the conditioned cell culture media through size exclusion chromatography and although we did not observe significant differences in particle quantity in the EV fractions, we did observe slightly smaller vesicles released from ER stressed cells compared to controls and strong expression of LC3B in the ER stress EVs. We also observed significant upregulation of miR-29a-3p in ER stress EVs when compared to controls. Taken together, these data suggest that ER stress negatively impacts production of key myelination proteins and induces cells to release EVs that may function to preemptively activate autophagic pathways in neighboring cells.